SERIOUS GAMES BERBASIS ROLE PLAYING GAME UNTUK MENGUKUR POTENSI PERILAKU CYBERBULLYING PADA SISWA SEKOLAH MENENGAH PERTAMA - Miftahul Munawaroh; Purwono Hendradi; Dimas Sasongko; Andi Widiyanto; Mukhtar Hanafi (Prodi Teknik Informatika, Fakultas Sains dan Teknologi, 2026)
Cyberbullying among junior high school students is a problem that is difficult to identify early because it occurs in the digital space and is hidden. This article aims to develop and test an educational game based on a Role Playing Game (RPG) as an instrument to measure the potential for cyberbullying behavior in junior high school students. The study used a Research and Development method that includes needs analysis, system design, application development, and product dissemination. The game was developed based on the Illinois Bully Scale indicators implemented in 18 interactive scenarios with a standardized decision-making mechanism and scoring system. Evaluation was carried out through expert validation using the Technology Acceptance Model, which includes aspects of perceived usefulness, attitude toward using, system relevance, and interface clarity. The results show that the developed educational game is considered feasible and relevant as a technology-based assessment medium to identify potential cyberbullying behavior and support educational management at the junior high school level.